Distribution of the Critically Endangered Giant Guitarfish (Glaucostegus typus) based on Local Ecological Knowledge in the Andaman Islands, India. (1st April 2022) - Nazareth, Evan; D'Souza, Elrika; Arthur, Rohan; Jabado, Rima W.
Abstract: For elusive, data-poor marine fauna, Local Ecological Knowledge (LEK) can be a rich and often underutilised source of biological and ecological data. We used a socio-ecological approach to assess LEK and provide key insights into the distribution, habitat use pattern, and threats facing giant guitarfishes ( Glaucostegus spp . ) in the Andaman Islands, India. We interviewed 175 fishers and other coastal users (SCUBA divers, coastal residents, researchers etc.), 142 of whom had seen giant guitarfishes. Due to the difficulty in distinguishing between species of this genus, this study did not attempt to collect species specific data. However, data presented here most likely refer to the Giant Guitarfish ( Glaucostegus typus ) as it is the only species from this family confirmed from the Andaman Islands. Our results show that LEK can be an invaluable asset in understanding the distribution of little-known species. With sightings from over 70 locations, our data indicate that giant guitarfishes occur widely and the frequent sightings of pup-sized (<45 cm) individuals in shallow coastal waters suggests they could be using these habitats as nursery grounds. The identification of several potential nursery areas highlights locations of their range that need urgent protection to aid in their conservation. The only other location where G. typus is reportedly still frequently observed is northern Australia, making the Andaman Island population globally significant. However, rapid coastal transformation and growing fisheries likely threaten the species. With more than 33% of reported observations being over a decade old, our data suggest that populations have drastically declined, highlighting the need to regulate fisheries and coastal development in the Andamans. Including giant guitarfishes under the Indian Wildlife Protection Act would also be an essential step towards managing this globally important population. Highlights: Local Ecological Knowledge provided baseline data on giant guitarfishes in India. Identification of critical giant guitarfish habitats can aid in their conservation. Our data suggest that juveniles may use shallow coastal waters as nursery grounds. If protected, the Islands could be a hotspot for these Critically Endangered species.